Phytochemistry and pharmacology of Pyrostegia venusta: a plant of Family Bignoniaceae - AVNISH KUMAR,; Monika Asthana,; Purbi Roy,; Sarika Amdekar,; Vinod Singh, (International Journal of Phytomedicine, 2013)
Worldwide over 80% population have dependence on natural resources (esp. plants) for treatment of disease, either due to drug resistance diseases or side effects of synthetic drugs. Hence, in recent years, ethano-medicinal studies have been acknowledged to evaluate plants products in modern scientific lines of phytochemical analysis, pharmacological screening and clinical trials. This review provides information on the botanical description, traditional uses, phytochemistry and pharmacology of one such important plant, Pyrostegia venusta. That has folkare tradition of medicinal use.